Body works - Cooley, Dennis, 1944- (Brave & brilliant series, 2023)
"A humorous, tender, irreverent, and meditative examination of the human body as it passes through time, and as it is celebrated and denied. The body may be feared. It may be a site of philosophic and theological weakness, a place of fear and contamination. The body may be weak. It is ephemeral and impure compared to what is supposed in an abstracted world of pure intellect. The body may be an obsession, a material concern taken up to the detriment of all else. The body may be a challenge to overcome, an enemy to silence. In this book, dennis cooley sympathizes with the body. These poems celebrate the yearning, laughing, hurting, tender body. Here, the body is neither a site of conflict nor a place of spiritual weakness, but instead a vessel of experience that works in harmony with the intellect. Bodies burble, rejoice, yearn, and suffer. Bodies grow old, they are injured, they hold strength and grow weak in unexpected ways. Rejecting the simplicity of transcendence for a nuanced examination of mortality, time, illness, of the things the body promises and the promises the body keeps, cooley is unafraid to challenge the eternal and the certain. These poems are humorous, intelligent, and poignant. body works is essential reading for anyone who lives inside a body that lives within the world."--